Prognostication of 600 meters race results of girls of 7-10 years - Samokih I.I (Kharkov National Pedagogical University, 2010)
Functional dependence of results is exposed in at run on 600 m. from the indexes of physical development, physical preparedness of girls. Also from - parameters of functional possibilities cardiovascular and central nervous systems of girls. Possibility of receipt of results of the pedagogical testing a calculation method is rotined about the level of endurance. Leading sufficient reliability of prognostication of results indexes are set in at run on distance 600 m. In an experiment 90 girls took part 7-10 years.